Table of Content - -, (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content1. The Prophetic Hadith as evidence for GrammarCo-Prof. Ibrahim Sulaiman Ibrahim Almatroudi2. Reasoning and its impact on grammatical thoughtMr. Majid Mohammad Al-Mozainy3. Covenant “Lam” and Gender “Lam” in the Holy Quran in light of Al-Baydawi's interpretation: Linguistic study of selected wordsDr. Mkhled Salman Obid Al-Maaitah4. Semantic Evolution of Terms during COVID: (Prototype of Ministry of Health’s Tweets)Mrs. Latifah Awwadhah Al-Mutairi5. Extrapolation of the image of the motherhood of the bird in Al-Qama Al-Fahl's DiwanLecturer \ Amani Saud Khishan Al-Qurashi6. Semiotic connotations in the Arabic novel The Baghdad Morgue, for exampleDr. Itidal Salman Iraby, Dr. Sura Saleem Abdel Shaheed7. Criticism of the Language of the Common People in Al-Misbāh Al-Munīr by Al-Fayoumi (770 AH)Mrs. Maha Abdulaziz Al-Essa
Keywords: Journal of Arabic Language and Literature